ابن الكردبوس (ت نهاية القرن السادس أو بداية السابع الهجريين) منهجه وموارده في كتابه الاكتفاء في اخبار الخلفاء - محمود حمادي, ايمان; حامد جاسم حمادي, علاء (Al-Adab Journal, 2018)
In this research, we will examine the life of a historian of the Arab Maghreb in the sixth century AH, namely, Abu Marwan Abdul Malik bin Abi Qasim Mohammed bin Al-Kordobos Al-Tozari, where he divided the research into two topics: The first topic was devoted to know about the life of the historian and about his age, And about his sheikhs, his travels, his writings and his death. The second study is devoted to studying the approach of the historian in his book "Sufficiency in the news of the caliphs." The research shows that the style of Ibn al-Kordobus was clear in his words in his expressions, which reveals the literary and scientific level that was high, which helped him to absorb what he mentioned his resources, In his formulation in a clear and precise way to fulfill the purposes that he intended to achieve from the writing of his book.